Effectiveness of single‐ vs dual‐coil implantable defibrillator leads: An observational analysis from the SIMPLE study. (22nd April 2019) - Neuzner, Jörg; Hohnloser, Stefan H.; Kutyifa, Valentina; Glikson, Michael; Dietze, Thomas; Mabo, Philippe; Vinolas, Xavier; Kautzner, Josef; O'Hara, Gilles; Lawo, Thomas; Brachmann, Johannes; VanErven, Liselot; et al.
Abstract: Introduction: Dual‐coil leads (DC‐leads) were the standard of choice since the first nonthoracotomy implantable cardioverter/defibrillator (ICD). We used contemporary data to determine if DC‐leads offer any advantage over single‐coil leads (SC‐leads), in terms of defibrillation efficacy, safety, clinical outcome, and complication rates. Methods and Results: In the Shockless IMPLant Evaluation study, 2500 patients received a first implanted ICD and were randomized to implantation with or without defibrillation testing. Two thousand and four hundred seventy‐five patients received SC‐coil or DC‐coil leads (SC‐leads in 1025/2475 patients; 41.4%). In patients who underwent defibrillation testing (n = 1204), patients with both lead types were equally likely to achieve an adequate defibrillation safety margin (88.8% vs 91.2%; P = 0.16). There was no overall effect of lead type on the primary study endpoint of "failed appropriate shock or arrhythmic death" (adjusted HR 1.18; 95% CI, 0.86‐1.62; P = 0.300), and on all‐cause mortality (SC‐leads: 5.34%/year; DC‐leads: 5.48%/year; adjusted HR 1.16; 95% CI, 0.94‐1.43; P = 0.168). However, among patients without prior heart failure (HF), and SC‐leads had a significantly higher risk of failed appropriate shock or arrhythmic death (adjusted HR 7.02; 95% CI, 2.41‐20.5). There were no differences in complication rates. Conclusion: In this nonrandomized evaluation, there was no overall difference in defibrillation efficacy, safety, outcome, and complication rates between SC‐leads and DC‐leads. However, DC‐leads were associated with a reduction in the composite of failed appropriate shock or arrhythmic death in the subgroup of non‐HF patients. Considering riskier future lead extraction with DC‐leads, SC‐leads appears to be preferable in the majority of patients.